Development of a knowledge test about scientists for secondary school students - Yildirim, Pelin; Kececi, Gonca; Zengin, Fikriye Kirbag (Izzet Kara, 2024)
This study aims to develop a knowledge test to assess secondary school students' awareness of scientists. After determining the topics that the questions in the test would measure, 50 multiple-choice questions were prepared and presented to six experts in the field. Following the experts' feedback, the number of questions in the test was reduced to 44 due to issues related to question clarity, alignment with the curriculum, and cognitive appropriateness. The 44 -question test underwent item analysis. The prepared test was subjected to a preliminary pilot application with 222 secondary school students. As a result of the preliminary pilot application, two questions with discrimination indices of 0.19 or lower were removed, and the final version of the test was arranged to consist of 42 questions for the pilot application. The pilot application was conducted with 211 secondary school students. In this application, secondary school students were administered the Knowledge Test of Scientists consisting of 42 questions, and item analysis was performed again. Two questions with discrimination indices of 0.19 or lower were removed from the pilot application. As a result of the pilot application, the Knowledge Test of Scientists had a KR -20 reliability coefficient of 0.94, and the Spearman Brown two -half test correlation coefficient was calculated as 0.92. The final version of the scale was arranged to consist of 40 items. These results demonstrate that the test is highly reliable, meaning that the test results accurately reflect the measured attribute and are replicable.
Keywords: Scientists; Knowledge test; Secondary school students; Scale development; Reliability.